Low-profile patch antennas with enhanced horizontal omnidirectional gain for DSRC applications - Liu, Ankang (2018)
Here, a low-profile microstrip patch antenna with vertical polarisation and over 3 dB enhanced gain in the horizontal plane is proposed for dedicated short-range communications (DSRC) application. It is a centre-fed circular patch antenna coupled by an annular ring and shorted concentrically with a set of shorting vias. For further increasing the gain in the horizontal plane, six groups of microstrip patches with one edge open and three edges shorted, which work as magnetic dipole antennas, are laid around the shorted circular patch-ring antenna (SCPRA). These gain enhancement elements resonate at 5.9 GHz and guide the TM wave along the horizontal surface. In addition, an equivalent circuit model of SCPRA is presented as a tool for easier impedance matching. The number of gain enhancement elements in each group can be adjusted to achieve variable radiation patterns in the horizontal plane. Two antennas achieving omnidirectional and quasi-elliptical radiation patterns are proposed, simulated, and measured. The measured results agree well with the simulated results, and the quasi-elliptical radiation patterns in the horizontal plane of the antenna demonstrate the desirable performance for DSRC applications.